2019
DOI: 10.28945/4297
|View full text |Cite
|
Sign up to set email alerts
|

Transition to First Year University Study: A Qualitative Descriptive Study on the Psychosocial and Emotional Impacts of a Science Workshop

Abstract: Aim/purpose The purpose of this article is to discuss the psychosocial and emotional outcomes of an introductory health science workshop designed to support and assist incoming health science students before starting their university study.   Background For the past two decades, a South Australian university offered an on-campus face to face workshop titled ‘Preparation for Health Sciences’ to incoming first-year students from eleven allied health programs such as Nursing, Physiotherapy and Medical Imaging. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…ScienceReady was developed as a preparatory course for new students commencing allied health degrees at UniSA and has been successfully running for over 20 years. The purpose of ScienceReady is to provide not only an introduction to the sciences and self-directed university study, but arguably more importantly, benefit the psychosocial and emotional aspects often associated with transition to University (Thalluri & Penman 2019). This is especially useful for students who find themselves particularly prone to disengagement and withdrawal, including students belonging to minority groups such as Aboriginal and Torres Strait Islanders, first in family to attend University, mature-aged students, and students living remotely or studying externally (Australian Government Department of Education and Training, 2017;Celli, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ScienceReady was developed as a preparatory course for new students commencing allied health degrees at UniSA and has been successfully running for over 20 years. The purpose of ScienceReady is to provide not only an introduction to the sciences and self-directed university study, but arguably more importantly, benefit the psychosocial and emotional aspects often associated with transition to University (Thalluri & Penman 2019). This is especially useful for students who find themselves particularly prone to disengagement and withdrawal, including students belonging to minority groups such as Aboriginal and Torres Strait Islanders, first in family to attend University, mature-aged students, and students living remotely or studying externally (Australian Government Department of Education and Training, 2017;Celli, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that attending ScienceReady improved student confidence and preparedness to start university, reduced anxiety, and that students were able to advance their basic understanding of biological principles (Thalluri, 2016;Thalluri & Penman, 2019).…”
Section: Introductionmentioning
confidence: 99%